The Implementation of HelloTalk Application in Vocabulary Teaching for Senior High School - Siregar, Winda Rahmana; Ismahani, Siti (Universitas Negeri Semarang, 2024)
This research aims to understand the effectiveness of the HelloTalk application in teaching English vocabulary for second grade high school students and its application in teaching English vocabulary. This research uses questionnaires, interviews and descriptive analysis methods to collect information about research and students’ experiences in learning English. The questionnaire covered what they knew about the HelloTalk application before and how they saw the application, whether the HelloTalk application was effective in teaching vocabulary and how to apply the application and the questionnaire was distributed via Google Forms after students had experience with HelloTalk. The research concluded that the Hellotalk application was effective in improving second grade high school students’ English learning, making the learning process more interactive and useful. This also helps improve the integration of applications in the curriculum to improve the quality of language learning and students’ learning experience.